Carlsberg alibi marketing in the UEFA euro 2016 football finals:Implications of Probably inappropriate alcohol advertising - Murray, Rachael; Opazo-Breton, Magdalena; Britton, John; Cranwell , Jo; Braham, Bruce (BMC Public Health, 2018)
Background: Alcohol advertising is a key driver of alcohol consumption, and is prohibited in France by the Loi Evin. In 2016 the Danish brewer Carlsberg sponsored the UEFA Euro 2016 finals, held in France, and used the alibis 'Probably' and '.the best in the world' in place of Carlsberg in pitch-side advertising. We have quantified the advertising exposure achieved during the final seven games in the UEFA Euro 2016 championship. Methods: Appearances of the Carlsberg alibis 'Probably' and 'the best in the world' were counted and timed to the nearest second during all active play in live coverage of quarter final, semi-final and final matches broadcast in the UK. We used census data and viewing figures from Kantar Media to estimate gross and per capita impressions of these advertisements in the UK population. Results: In 796 min, 29 s of active play there were 746 alibi appearances, totalling 68 min 35 s duration and representing 8.6% of active playing time. Appearances were particularly frequent at the end of normal time, extra time and penalties. The seven matches delivered up to 7.43 billion Carlsberg alibi impressions to UK adults and 163.3 million to children. In the only match involving a second country with laws prohibiting alcohol advertising (France versus Iceland), exposure occurred for only 1.8% of playing time. Conclusions: Alibi marketing achieved significant advertising coverage during the final seven EURO 2016 championship games, particularly to children. Since 'Probably' is registered by Carlsberg as a wordmark this advertising appears to contravene the Loi Evin, though Carlsberg have defended their marketing actions.